THE IMPACT OF SOCIAL MEDIA ON ADOLESCENT MENTAL HEALTH (Journal of Medical & Health Sciences Review, 2025)
The unprecedented increase in social media use has changed the psychosocial environment of teenagers, redefining the communication, identity construction, and emotional satisfaction. This paper examines how social media use has a complex influence on the mental health of adolescents focusing on behavioral, emotional, and cognitive levels. To determine the association between social media exposure and the development of psychological consequences, such as depression, anxiety, self-esteem and social connectedness, the research used a cross-sectional mixed-method design. Standardized psychological scale quantitative data were supplemented with qualitative data (focus group interviews) to obtain subjective data. The results show a high level of correlation between high-frequency use of social media and indicators of anxiety, depressive symptoms, and negative body image perception. On the other hand, moderate and intentional participation also enhanced better social belonging and access to peer support networks. There were differences along gender and age lines, with the young teenagers and the female gender exhibiting a greater degree of emotional vulnerability. The paper presents the dualism of social media as a possible risk factor and coping strategy and suggests the need to establish a balanced use pattern and digital literacy training. These lessons add to the emerging literature on the topic of adolescent digital mental health and can be used in the design of interventions that encourage psychological resilience during the digital age.